Modern education «in the clutches» of liberal market extremism - Kirvel, Cheslav S. (Journal of the Belarusian State University. Sociology, 2019)
The article grounds the idea that the process of reorganization and reformation of educational practices in most non-European countries, including former Soviet countries, are implemented mainly in the interests of transnational capital and business that threaten countries’ national-state security. This situation provides the reason for total commercialization of educational systems of the former Soviet Union states, persistent attempts of elimination of traditional educational models, their replacement with education market, endless reforms, reorganizations, «optimization», etc. It is emphasized that embedding of educational institutions in transnational business structures significantly expands possibilities of «transfer of brains» and the latest scientific developments to the West. The emphasis is placed on the fact that in the conditions of modern global capitalism the issues of social and state control over the processes in education and scientific sphere is extremely urgent.
Keywords: education; system crisis; transnational corporations; business; market pedagogy; academic capitalism; undermining innovations; educational services; competence approach; national security; bureaucracy; social humanitarian factor of development